We Must Prioritize Making Childbirth Safe and Equitable. Issue 2 (March 2022) - Killion, Molly M.
Abstract : Maternal mortality rates in the United States compare very unfavorably to peer countries. The United States has seen maternal mortality rates continue to rise, while other peer countries and developing countries have reported decreases. Our maternity nursing expert, Molly Killion, reports on recent evidence about maternal mortality in the United States and how nurses can promote improved maternity care for all those who give birth.